Angular distributions of parametric X-ray radiation from a diamond crystal; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 402 - Takabayashi Yu. Yushi; Korotchenko K. B. Konstantin Borisovich; Pivovarov Yu. L. Yury Leonidovich; Tukhfatullin T. A. Timur Ahatovich (2017, 2017)
Title screen